Ilíada XXII 98-130: el soliloquio de Héctor o la definición discursiva del "héroe del aidós" (Argos, 2025)
This study aims at approaching to one of the most significant iliadic passages: the soliloquy that makes Hector, the greatest Trojan hero, just before the last and most important singular combat in the poem, in Book XXII (98-130). We will try to prove –by means of its philological-literary analysis– the importance of his words to build an alternative heroic model –as opposed to the character of Achilles, "the best of the Achaeans"– to whom his duties as a hero, moreover the pressure exerted on him by his social environment, become together his own death sentence.
Keywords: soliloquy; hero; aidos; thymos; free will